A "Park to Live" between environmental education and social inclusion through a landsense ecology approach. Issue 2 (17th February 2021) - Tarsitano, Elvira; Posca, Cecilia; Giannoccaro, Rosa, Alba; Borghi, Carolina; Trentadue, Consiglia; Romanazzi, Giovanna; Colao, Marcello
ABSTRACT: A 'Park to Live', a social inclusion project with the aim of making socially active a heritage of high natural and landscape value, such as the Regional Natural Park of Lama Balice, located in the city of Bari (Apulia Region, Italy), through the introduction and testing of environmental and green healing activities for the psycho-physical well-being of users with mental illness. The spaces surrounding Villa Framarino, building owned by the Municipality of Bari, lead authority of the Park, have become an 'open-air' laboratory to enhance the potential skills and manual and psycho-physical ones of the participants, through agricultural activities as orthotherapy and environmental education experiences with sensory laboratories in a perspective of landsense ecology toward sustainable development. Recent studies on Landsense ecology have highlighted how urban parks not only improve urban ecosystems, but also provide cultural values to city dwellers. The use of perceptual indicators and perception itself increases visitor satisfaction. Furthermore, the more a territory is urbanized, the more citizens prefer natural landscapes. In particular, in a recent paper, the authors highlight the relationships between sustainable development, landsense creation and ecosystem services. This work is based on this approach in order to develop environmental activities; to experiment an innovative networking system for the sustainable development of the territory; to promote a sustainable lifestyle through specific sensorial and relational experiences that increase self-awareness and spread self-responsibility aimed at protecting the natural environment of the Park.